Primary cutaneous lymphomas in children: A prospective study from the Spanish Academy of Dermatology and Venereology (AEDV) Primary Cutaneous Lymphoma Registry. Issue 6 (11th October 2021) - Torre‐Castro, Juan; Estrach, Teresa; Peñate, Yeray; Acebo, Elvira; Fernández de Misa, Ricardo; Blanes, Mar; Suh‐Oh, Hae Jin; Botella‐Estrada, Rafael; Torrelo, Antonio; García‐Doval, Ignacio; Machan, Salma; ,
Abstract: Background/Objectives: Primary cutaneous lymphomas are rare in pediatric patients. The clinical and histopathological manifestations may differ from those in adults. Due to their low frequency and the insidious clinical picture, the diagnosis is usually delayed. The Spanish Primary Cutaneous Lymphoma Registry was initiated in 2016 as a multicenter registry that would allow better insight into the epidemiological, clinical, histopathological, and treatment response characteristics of patients with primary cutaneous lymphomas. Methods: We conducted a prospective observational cohort study of primary cutaneous lymphomas in pediatric patients participating in the Spanish Academy of Dermatology and Venereology (AEDV) Primary Cutaneous Lymphoma Registry. Results: At the time of the analysis, 10 patients under 18 years of age out of 799 all‐age cases (1.25%) had been included in the registry (7 males, 3 females). The mean age at diagnosis was 9.7 years (SD: 4.8). Seven (70%) had mycosis fungoides, 2 of them had the folliculotropic variant; and 3 (30%) had primary cutaneous marginal zone B‐cell lymphoma. Conclusions: Primary cutaneous lymphomas are extremely rare in pediatric patients and usually have a good prognosis. Therefore, a high level of suspicion is necessary for the diagnosis. We suggest management by experienced physicians and follow‐up into adulthood.